Mission in covid/post-covid times Drawing inspiration from pope Francis - Catalano , Roberto (Studia Theologica Varsaviensia, 2022)
In Bergoglio’s thinking, to build on fraternity in order to create a culture of encounter and justice means to move together towards unity, which helps to be committed “to allow people to serve as a body despite differences of viewpoint, physical separation and human ego”.[1] This attitude and these commitments will prevent us from falling into uniformity while respecting the values and richness of plurality. In fact, in today’s world, while we are more and more interconnected we experience a deep sense of division, especially at the social and economic level. Our societies and communities are more and more fragmented and this creates dangerous polarizations, as it is seen in politics and social life. Fraternity will help to foster dialogue at all levels and this will enable people “to generate a shared horizon toward which we can all move forward together”.[2] This does not mean, in Pope Francis’ understanding, denying tensions and differences. It rather calls for the engagement of everyone and all communities to work for a wider unity where all differences remain and coexist while working together. This reading of the present reality can help us react to the pandemic as a people, as a whole humanity with its differences and riches. But we need the courage “to restore an ethics of fraternity and solidarity, regenerating the bonds of trust and belonging. For what it saves is not an idea but an encounter.” [1] Ibid., p. 68. [2] Ibid., p. 76.